EXPLORATORY STUDY OF SPIRITUALITY IN THE WORKPLACE - Pérez Santiago, José Armando (Anales de Psicología / Annals of Psychology, 2007)
This study was carried out to identify the perceptions of a group of employees in relation to the subject of spirituality and spirituality at work. A total of 250 employees participated in this study. The Cuestionario sobre Espiritualidad en el Trabajo was use to recollect the data. The research design use was the expo-facto. The results showed that the spiritual dimen-sion is important for the majority of the employees. The most mentioned activities to stimulate the growth and development of this dimension were the reading of new age books, listening relaxation music and involving in charity activities. In relation to the subject of work spirituality, the majority of the employees mentioned that their jobs should provide them with opportunities for personal and spiritual growth and development. Also, the majority mentioned that the subject of spirituality should be discussing openly in the workplace. These results were discussed considering the studies about this topic and its possible applications in the work context.